Clinical Application of Renograph IR-03 for the Hospital - R. Isaris; J. Sumanto; Suharni Suharni; P. Bagaswoto; E. Purwanti (Atom Indonesia, 2012)
The renography using renograph is one of clinical modality to investigate the renal function among other such as laboratory medical check up and X-rays. The prototype of renograph IR-03 designed by BATAN has been constructed and the laboratory tests as well as clinical tests have been carried out at PRPN-BATAN Serpong and General Hospital Dr. Sardjito Jogyakarta, respectively. Cost associated with the clinical use of renograph at the hospital are analyzed according to the two major components: radiopharmaceutical cost and the use of equipment. Annual cost of operational of renograph by estimate number of patient is about 2,000 is IDR. 30.0 millions for radiopharmaceutical 131Iodine. Total Direct Cost is about IDR. 212.5 millions and the Capital Cost for one unit renograph is IDR. 250 millions. The Break Event Point of invest one unit renograph is 1194 procedures (0.597%), or about IDR. 209,475 millions, which the cost for each procedure is IDR. 85,000.-. This value is depending on several variables, especially number of procedure can be reached. The cash flow analyses by Rate of Return (ROR) showed that the value of i* is 22.6% is much greater than the value of MARR or saving rate of interest in the Bank now is about < 10%. The Payback Period calculation to see on how interesting the investment of renograph and its prospect for application in the hospitals showed about 1.818 years, that is good prospect economically. Received: 28 April 2011; Revised: 03 July 2012; Accepted: 07 July 2012